Irish physical force republicanism in Britain, 1919-1923 - Noonan, Gerard (Trinity College (Dublin, Ireland). Department of History, 2011)
This thesis studies the activities of Irish republicans - mainly the Irish Republican Army (IRA) - in Britain from the outbreak of the war of independence in 1919 to the end of the civil war in 1923. It is based on my reading of primary and secondary sources. The primary sources employed can be divided into two main types: those dating from the period under study and the recollections of veterans in later life. At University College Dublin Archives, 1 consulted the collections of Eamon de Valera, Sighle Humphries, Terence MacSwiney, Richard Mulcahy, Ernie O'Malley and Maurice ‘Moss' Twomey, all of which contain contemporaneous records detailing republican activities in Britain, as well as the transcripts of interviews with veterans decades later.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin